A polidez indiciando a multifuncionalidade do verbo achar - Santos, Juliana dos (2010)
This study aims to analyze multifunctionality find the verb to find, as a perspective for both synchronous and tested this hypothesis in the corpus of Portuguese spoken in the city of Vitoria (PORTVIX). In this study, we take as a starting point the multifunctionality studies that discuss the semantic change of lexical items that‘s a process of grammaticalization. Our look builds on the studies of Traugott and Dasher (2005) that deal with the process of grammaticalization, pointing the concept of subjectivity within this perspective. It was in observing the speaker to make use of the verb find express their individuality, expressing his opinion in speech, and also invites the recipient to take with him his vision. We find that the verb is an expression of politeness and, according to the corpus, much used by graduated ones. Perhaps it should be made for having the need of preservation of the face, that is, often away from a commitment to their statements or not to harm the image of itself neither the speaker. This work is justified to the extent that at the end of this, we will have a multifunctional display of the verb to think in PORTVIX.